Service quality and customer satisfaction in relationship in casual western dining restaurants in Malaysia - Saad, Mazni; Abukhalifeh, Alaa Nimer; Slamat, Syafiq Syaheer; TengkuYacob, Tengku Nor Farah Farhanah (APF 2019, 2019)
Many urban Malaysians are attracted to the moderately-priced food that is usually served in a casual atmosphere. Its popularity has given rise to its potential business in the foodservice industry. The sudden increase in the number of Casual Western Dining Restaurants (CWDR), however, creates a stiff competition which has resulted not only in a bad turnover of customers but also in businesses closing abruptly. Another reason for such closures is also the dissatisfied customers who experience poor quality service at these dining restaurants. Thus, the current study aims to examine the relationship between Service Quality (SERVQUAL) and Customer Satisfaction at CWDR. A total of 380 questionnaires distributed and yielded a 53 percent response rate. The SERVQUAL model contributed 76 percent of the variance in the customers’ satisfaction level among those who dined in the restaurants. The overall results show that in a highly competitive business environment, customers' evaluation of Service Quality and Customer Satisfaction is critical for the service restaurants' survival. The management must therefore focus on these most crucial factors that have enhanced service standards of CWDR. Also highlighted in this study are the limitations encountered and the possibilities for future research.